Carbon Sequestration Potential of Trees Planted Along Roadsides: A Case From Bhopal City, India - Dugaya, Dharmendra; Srirag, S.; Kumar Pandey, Ankit; Paul, Ankita; Dev Shukla, Deependra; Deo, Krishna; Sharma, Nidhi; Verma, Shivani; Nagaria, Shourya; Guhaprasad, Shruti; Chaudhry, Pradeep (International Journal of Environment, 2020)
In the present article, we have discussed one such example from Indian Institute of Forest Management, Bhopal campus where the amount of carbon stored, and carbon dioxide sequestered by the trees along roadside has been estimated. Importance Value Index was calculated separately for each species. Biomass and carbon stock of woody vegetation was assessed using a non-destructive method. Leucaena leucocephala, Schleichera oleosa, Dalbergia paniculata, Acacia catechu and Ficus religiosa recorded high biomass carbon content. The average stem density was 295 stems ha-1. Species-wise calculated average CO2 equivalent in the sample observed increasing trend with the increase in girth class from 20cm to 60cm but showing reduced trend in trees with girth class above 60 cm. The probable reason for reducing trend could be the variation in wood density of species towards the lower value of high girth size species such as Bombax ceiba, Samanea saman, Holoptelea integrifolia, Dalbergia paniculata, Lagerstroemia parviflora and Ficus religiosa. The analysis can be useful for selection of tree species with high wood density for planting in urban areas of central India to adequately mitigate pollution, especially the vehicular pollution. The incorporation of the same in the management plan of the urban green spaces would benefit the optimum utilization of carbon sequestration potential. Moreover, the suitable bamboo species, which is characterized as species of the understory of tropical dry deciduous forests, may be considered for the planting as gap filing and sequestration of carbon in urban areas.